Damage evaluation of proton irradiated titanium deuteride thin films to be used as neutron production targets - Suarez Anzorena, Manuel (2018)
Titanium deuteride thin films have been manufactured under different conditions specified by deuterium gas pressure, substrate temperature and time. The films were characterized by different techniques to evaluate the deuterium content and the homogeneity of such films. Samples with different concentrations of deuterium, including non deuterated samples, were irradiated with a 150 keV proton beam. Both deposits, pristine and irradiated, were characterized by optical profilometry and scanning electron microscopy.